The Lost of Virtual and Simulated Identity in Online/Virtual Platform Written Adaptation of a Game “Digimon Story Cyber Sleuth: Hacker’s Memory” - Richard Lawrence; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2020)
This creative project is a written adaptation of a video game entitled Digimon story Cyber Sleuth: Hacker’s Memory (2017). This adaptation will retell a story from the aforementioned video game title about an alternate Japanese society where technology has evolved so much that people can dive into a cyber space called EDEN. By using a set of computers and a special device called Digivice. In this virtual cyberspace, a physical manifestation can be achieved by having a virtual account and many people at the beginning of the story have been using EDEN for years to do many things. The story begins with a young man who lost his virtual account. In order to get his account back he has to get involved in the world of hackers which are individuals who are able to temper the programming codes of EDEN just like how it used to be in regular computers to achieve a certain purpose. In this involvement the protagonist also encounters creatures known as Digimon which will then play a major role in the story moving forward. The protagonist also meets a hacker group called Hudie which the protagonist ends up joining in order to gain support in searching for his missing account. The theme of this adaptation is how a missing a virtual identity ends up shaping another identity for the main protagonist. This adaptation also serves as a journey for the main protagonist who at the beginning falls under the category of “hacker” which is a bad term into a “hero” at the end. Key words: Virtual, cyber space, hacker, mental data, avatar, account, identity.